Telecommunications: Maine's Best Kept Secret - Silkman, Richard (Maine Policy Review, 1993)
This article is based on a presentation at the Pure '93 Conference last January. Richard Silkman discusses Maine's recent policies on telecommunication. Silkman, as Governor John McKernan's Director of the State Planning Office, was often the lead spokesman on telecommunications policy for the current governor. The analysis of telecommunications policies of the two recent Maine gubernatorial administrations [Brennan and McKernan] reveals a surprisingly common core over the entire period since the AT&T divestiture.
Keywords: Maine; telecommunications policy